Pengaruh Current Ratio, Earnings Per Share dan Debt To Equity Ratio Terhadap Harga Saham Pada PT. Mitra Adiperkasa Tbk Periode 2014-2023 - Nur Anisa (PT. Hasba Edukasi Mandiri, 2025)
This study aims to determine the effect of the Current Ratio, Earnings Per Share, and Debt to Equity Ratio influence Stock Prices at PT Mitra Adiperkasa Tbk for the 2014-2023 period. This research employs a descriptive quantitative method with hypothesis testingThe t-test results show that partially, the Current Ratio does not influence Stock Prices (t-value: -1.240 < 2.447, significance: 0.261 > 0.05), Earnings Per Share has a positive effect on Stock Prices (t-value: 2.606 > 2.447, significance: 0.040 < 0.05), and the Debt to Equity Ratio does not influence Stock Prices (t-value: -2.280 < 2.447, significance: 0.063 > 0.05). Simultaneously, the Current Ratio, Earnings Per Share, and Debt to Equity Ratio significantly influence Stock Prices at PT Mitra Adiperkasa Tbk, as indicated by an R-square value of 0.699, an F-value of 6.049 > 4.76, and a significance level of 0.030 < 0.05. These findings reveal that the Current Ratio, Earnings Per Share, and Debt to Equity Ratio collectively explain 75.2% of the variance in Stock Prices, with the remaining 24.8% influenced by variables outside this study.